1991
DOI: 10.1105/tpc.3.11.1177
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome-Deficient hy1 and hy2 Long Hypocotyl Mutants of Arabidopsis Are Defective in Phytochrome Chromophore Biosynthesis.

Abstract: The hy1 and hy2 long hypocotyl mutants of Arabidopsis contain normal levels of immunochemically detectable phytochrome A, but the molecule is photochemically nonfunctional. We have investigated the biochemical basis for this lack of function. When the hy1 and hy2 mutants were grown in white light on a medium containing biliverdin IX[alpha], a direct precursor to phytochromobilin, the phytochrome chromophore, the seedlings developed with a morphological phenotype indistinguishable from the light-grown wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 9 publications
10
127
0
2
Order By: Relevance
“…Their hypocotyl lengths were not reduced by the application of biliverdin but in fact were even longer than their negative controls. In contrast, the phytochrome chromophore mutant hyl (Koornneef et al, 1980) was reduced to a similar leve1 to that of wild-type seedlings, as shown previously (Parks and Quail, 1991). These results indicate that the phenotype of the PHYl transgenic plants is not a consequence of reduced chromophore availability for the endogenous PHYA in the transgenic plants.…”
Section: --supporting
confidence: 45%
“…Their hypocotyl lengths were not reduced by the application of biliverdin but in fact were even longer than their negative controls. In contrast, the phytochrome chromophore mutant hyl (Koornneef et al, 1980) was reduced to a similar leve1 to that of wild-type seedlings, as shown previously (Parks and Quail, 1991). These results indicate that the phenotype of the PHYl transgenic plants is not a consequence of reduced chromophore availability for the endogenous PHYA in the transgenic plants.…”
Section: --supporting
confidence: 45%
“…The mutant screen is based on the selection for survivors of allyl alcohol treatment of mutagenized Arabidopsis lines containing a CAB3 promoter fused to the ADH gene, thus allowing the identification of mutants-independent of phenotype-in which a tightly regulated light-controlled promoter is expressed at low levels in the light. Our data indicate that the screen is robust, resulting in mutations in at least 11 independent cue loci (E. Lopez and J. Chory, unpublished results), including loci encoding the apoprotein component of phytochrome 6 (Reed et al, 1993), and the synthesis of the linear tetrapyrrole common to all phytochromes, hyl (Koornneef et al, 1980;Parks and Quail, 1991). The fact that we found photoreceptor mutations indicates that we might recover alleles in all of the positively acting components of phytochrome signaling of CA5 gene expression.…”
Section: Discussionmentioning
confidence: 74%
“…These mutants, including six hy loci and three blu loci, develop long hypocotyls in the light. Mutants in three of these loci (hyl, hy2, and hy6) are deficient in functional phytochrome due to a defect in the biosynthesis of the phytochrome chromophore (Parks and Quail, 1991;Chory, 1992). Mutations at the hy3 locus cause a specific reduction in type B phytochrome (Somers et al, 1991).…”
Section: Introductionmentioning
confidence: 99%